1-(9H-Carbazol-4-yl-oxy)-3-{[2-(2-meth-oxy-phen-oxy)eth-yl]amino} -propan-2-ol hemihydrate: A carvedilol solvatomorph - Díaz, Fernando (2011)
In the title racemic hemihydrated solvatomorph of carvedilol (carv), C 24H26N2O4·0.5H2O, the asymmetric unit contains two independent organic moieties and one water mol-ecule. Within this 2(carv)·H2O unit, the mol-ecular components are strongly linked by hydrogen bonds and the unit acts as the basic building block for the crystal structure. Inter-actions parallel to (10) generate hydrogen-bonded layers which are further linked by much weaker C-H⋯N/O inter-actions. The con-for-mations of the organic molecules, as well as the hydrogen-bonding inter-actions connecting them, are compared with other related structures in the literature.